1966
DOI: 10.1002/pen.760060317
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation of semicrystalline polyethylene

Abstract: Thermal oxidation in linear polyethylene is mainly confined to disordered regions in which scission reactions cause crystallization and eventual deterioration of mechanical properties. Gel formation is negligible at 100°C. As degradation proceeds, comparable changes occur in the intrinsic viscosities of melt and solution‐crystallized liner polymers, indicating that chain folds are regularly arranged and are resistant to oxidative scission. Breakdown is much more extensive in branched and crosslinked polymers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1969
1969
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Hence, a small degree of oxidation in the amorphous regions can dramatically change the polymer properties (Scheirs 2000). Winslow et al (1966) observed that oxidation in the amorphous region can lead to crystallinity increase in these regions due to scission of constrained chains in the amorphous material allowing the resulting freed segments to crystallise. In addition, Luongo (1963) showed an increase in crystallinity of linear and branched polyethylene followed the increase in the oxidation due to the replacement of C-H bonds by C-O bonds in the amorphous phase.…”
Section: Changes In the Polymer Morphology Due To Chemical Degradatiomentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, a small degree of oxidation in the amorphous regions can dramatically change the polymer properties (Scheirs 2000). Winslow et al (1966) observed that oxidation in the amorphous region can lead to crystallinity increase in these regions due to scission of constrained chains in the amorphous material allowing the resulting freed segments to crystallise. In addition, Luongo (1963) showed an increase in crystallinity of linear and branched polyethylene followed the increase in the oxidation due to the replacement of C-H bonds by C-O bonds in the amorphous phase.…”
Section: Changes In the Polymer Morphology Due To Chemical Degradatiomentioning
confidence: 99%
“…Although the notch (20% of the thickness in depth) in the SCR test tends to mitigate the effect of degradation from one surface, the degradation of the opposite surface of the GMB to the notch may decrease the resistance of the ligament behind the notch and facilitate the propagation of the crack from the root of the notch in the ligament and, if so, decrease the SCR when there is sufficient surface degradation. On the other hand, Winslow et al (1966) indicated that reduction in tensile strength of polyethylene due to slight oxidation could be also restored by melting and remoulding the specimen as melting of the broken chains due to localised degradation could be redistributed throughout the polymer mass. Thus, by analogy, a complete melt for 6 min in the MI test could average the effect of localised degradation throughout the thickness of the polymer and thus the MI test is expected to be less sensitive to early surface or near surface degradation than SCR.…”
Section: Surface Degradation and Scrmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation could be due to (i) chemical degradation of the polyethylene that involves oxidative degradation either by UV radiation (photo-oxidation) or thermal oxidation (Winslow et al 1966;Haxo and Nelson 1984;Haxo and Haxo 1989;Koerner et al 1990), which are considered to be the most harmful for HDPE GMBs exposed to the elements (e.g., Hsuan et al 1991;Rowe et al 2003), and (or) (ii) by a change in morphological structure of the GMB (Ewais and Rowe 2014b) that may result in increasing the GMB crystallinity (known as physical ageing of the GMB) as the polymer tends to be more glassy and less rubbery (Kovacs 1958;Struik 1977;Kubát et al 1989) and (or) decreasing the stress crack resistance of the GMB (Ewais and Rowe 2014b).…”
Section: Introductionmentioning
confidence: 99%